Emergency Department Use of Intravenous Prochlorperazine for Acute Migraine. (July 2018) - Cook, Calli; Newberry, Brittany
Abstract : The Research to Practice Column is designed to improve translational research critique skills of nurse practitioners (NPs). In this issue, the article "Randomized study of IV prochlorperazine plus diphenhydramine vs IV hydromorphone for migraine" is discussed in the context of a patient with an acute headache presenting to the emergency department (ED). The study was designed to assess the efficacy of intravenous prochlorperazine and diphenhydramine as compared with intravenous hydromorphone for patients with acute migraine in the ED. With the growing trend to avoid the use of opiates to curb potential addiction and increased ED length of stay, NPs need to be aware of efficacious, evidence-based treatments for acute migraines, a common ED presentation.